IMPLEMENTASI DAN KESIAPAN SEKOLAH DASAR DALAM MENYEGARAKAN PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students with special needs who often attend state elementary schools Difficulties faced in the learning process. There are so many things that hinder the implementation of inclusive education. This research aims to analyze implementing inclusive education for children with special needs in elementary schools. The research method or method in this research uses literature research. Data and information collection techniques through literature review. The results of the research state that formal elementary schools have provided inclusive education for Special Needs (ABK) children. However, in terms of readiness, it is still not optimal, because there is still a lack of contextually relevant teaching staff with adequate education so that when assisting children with special needs there are many challenges and obstacles. Based on the analysis of several related research journals, it can be said that all special education assistant teachers with special education degrees are still relatively small. Finally, most schools that provide inclusive education fulfill their tutoring and training obligations for students with special needs (ABK)